2017
DOI: 10.1098/rsos.170309
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and connectivity of tiger sharks (Galeocerdo cuvier) across the Indo-Pacific Ocean basin

Abstract: Population genetic structure using nine polymorphic nuclear microsatellite loci was assessed for the tiger shark (Galeocerdo cuvier) at seven locations across the Indo-Pacific, and one location in the southern Atlantic. Genetic analyses revealed considerable genetic structuring (FST > 0.14, p < 0.001) between all Indo-Pacific locations and Brazil. By contrast, no significant genetic differences were observed between locations from within the Pacific or Indian Oceans, identifying an apparent large, single Indo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 46 publications
5
36
0
Order By: Relevance
“…Microsatellite genotypes generated by Holmes et al. () and Bernard et al. () were also added to the present study (Figure ; Table ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Microsatellite genotypes generated by Holmes et al. () and Bernard et al. () were also added to the present study (Figure ; Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Using nine microsatellite loci, Holmes et al. () confirmed genetic isolation between the western Atlantic and the Indo‐Pacific. Further, the high connectivity around Australia found by Bernard et al.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Many species that are widely distributed and highly vagile exhibit little population structure and constitute a single panmictic population (Graves, 1998); however, previous studies of shark population structure have shown significant genetic subdivision at global (e.g. Bernard et al, 2016;Clarke et al, 2015) and regional scales (Domingues, Hilsdorf, Shivji, Hazin, & Gadig, 2018;Holmes et al, 2017;Karl et al, 2011;Karl, Castro, & Garla, 2012). Indeed, sharks have been the focus of many studies on migration and site fidelity, using traditional methods such as capture-tagging-recapture and acoustic tracking (e.g.…”
Section: Introductionmentioning
confidence: 99%